RISK FACTORS AND STRUCTURE OF DELAYS OF NERVOUS_PSYCHOLOGICAL DEVELOPMENT OF EARLY AGE CHILDREN: OPPORTUNITIES AND PROSPECT OF DIAGNOSTICS IN PEDIATRIC CARE - D.V. Kukushkin; T.A. Kuznetsova; T.M. Nechaeva (Union of pediatricians of Russia, 2008)
In conditions of a pediatric site at 114 children of early age psychological development on 5 spheres (motor, touch, cognitive, emotional, behavioral) are estimated. The somatic reason of a neurologic and behavioral development deviation in half of cases reveals the frequent respiratory disease. Deviations basically concern emotional and behavioral spheres on which as has shown questioning in 107 pediatricians, there is no due attention from local pediatricians. It does not justify expectation of parents (109 respondents) which harmonious development of all spheres of the child interest.Key words: neurologic and behavioral development at an early age, clinical psychological diagnostics, emotional and behavioral disorder, frequent respiratory diseases in children.